2022
DOI: 10.1111/insr.12522
|View full text |Cite
|
Sign up to set email alerts
|

ABC of the future

Abstract: Approximate Bayesian computation (ABC) has advanced in two decades from a seminal idea to a practically applicable inference tool for simulator-based statistical models, which are becoming increasingly popular in many research domains. The computational feasibility of ABC for practical applications has been recently boosted by adopting techniques from machine learning to build surrogate models for the approximate likelihood or posterior and by the introduction of a general-purpose software platform with severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
(158 reference statements)
0
8
0
Order By: Relevance
“…This intuitive method has been used for applied work by McKinley et al (2009), Canale and Ruggiero (2016), Pesonen et al (2022) but without detailed analysis. Frazier et al (2019) analyzed this approach theoretically and showed that under certain technical conditions the approximate posterior predictive in a sense coincidences with the exact one as the data size becomes arbitrarily large and as h → 0.…”
Section: Tractable Simulation From Conditional Predictive Densitymentioning
confidence: 99%
See 3 more Smart Citations
“…This intuitive method has been used for applied work by McKinley et al (2009), Canale and Ruggiero (2016), Pesonen et al (2022) but without detailed analysis. Frazier et al (2019) analyzed this approach theoretically and showed that under certain technical conditions the approximate posterior predictive in a sense coincidences with the exact one as the data size becomes arbitrarily large and as h → 0.…”
Section: Tractable Simulation From Conditional Predictive Densitymentioning
confidence: 99%
“…Despite substantive amount of research on ABC methodology and applications (see e.g. Marin et al 2012;Sisson et al 2019;Pesonen et al 2022) and the fundamental importance of prediction in statistical inference, the use of ABC in the context of predictive inference has not been widely studied. In this paper we investigate ABC as a generic technique to approximate the posterior predictive distribution of some future observations or missing data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the selection of summary statistics is an important issue when they are not sufficient for the given model. The ABC field has received many reviews due to its wide theoretical scope and applicability (e.g., Sunnåker et al 2013;Karabatsos & Leisen 2018;Sisson et al 2018;Grazian & Fan, 2020;Cranmer et al 2020;Craiu & Levi, 2022;Karabatsos 2023;Pesonen et al 2023;Martin et al 2023).…”
Section: Introductionmentioning
confidence: 99%